The Influence of Islamic Environmental Ethics on Business Decision-Making and Corporate Social Responsibility Practices - Dhety Chusumastuti; Ayu Lucy Larassaty; Vüqar Ahmad Mammadli (International Forum of Researchers and Lecturers, 2024)
This study explores the influence of Islamic environmental ethics on Corporate Social Responsibility (CSR) and business decision-making, emphasizing how faith-based ethical frameworks guide sustainable practices in contemporary corporate environments. Grounded in the principles of stewardship (khalifah), justice (adl), and collective welfare (maslahah), Islamic ethics provide a holistic model for aligning profitability with moral and environmental responsibility. Using a mixed-method approach that combines survey research and content analysis, data were collected from 50 Shariah-compliant and ethically oriented companies across multiple industries. The survey measured the integration of ethical values into CSR initiatives, while content analysis of corporate reports evaluated transparency, environmental commitment, and ethical disclosures. The findings reveal that organizations adhering to Islamic ethical principles exhibit stronger environmental accountability, higher ethical compliance, and more sustainable long-term strategies compared to secular firms. These companies perceive environmental responsibility as a moral obligation rather than a regulatory requirement, integrating ethical governance into daily operations and strategic planning. The results also highlight that employee engagement and stakeholder trust improve significantly when CSR activities are guided by Islamic values. Furthermore, case studies of Islamic banks and small-to-medium enterprises (SMEs) in Muslim-majority regions demonstrate practical applications of these principles, including the use of zakat and waqf funds for environmental initiatives and community development programs. The study concludes that embedding Islamic ethics into business operations fosters a balance between economic growth, social welfare, and environmental stewardship. It also provides a pathway for strengthening corporate integrity and long-term competitiveness. Future research is recommended to examine the applicability of Islamic ethical principles across different industries and explore their intersection with emerging areas such as green innovation, artificial intelligence governance, and digital finance. Overall, this research underscores the potential of Islamic ethics as a foundation for sustainable business models that harmonize spiritual and economic objectives.